Potential for Developing Rabbit Farming Business in Salokaraja Village, Lalabata District, Soppeng Regency - Utami, Sri Wira; Sonjaya, Herry; Tullah, Muh. Firdaus; Irwan, Irwan; Damayanti, Erni; Aksan, Muhammad; Rahmat R., Muh. Faisal (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2024)
Rabbits can give birth 6 – 8 times a year with a gestation period of approximately 30 days. Each time she gives birth, the number of children produced can reach 8 per mother. The rabbit farming business is used as income for business sustainability and development, as well as to meet daily needs. The data obtained was processed descriptively to describe the potential conditions for rabbit livestock development in Salokaraja Village, Lalabata District, Soppeng Regency. The results show that in the village there is a very high potential for development considering the large potential of natural resources which consist of large areas of land, the climate is on high ground with relatively low temperatures, and food that is easily obtained, namely forage and agricultural waste. Likewise, human resources consist of a high population with only a small number of rabbit breeders so there is less competition, the relatively large number of livestock owners only needs to be further developed, especially in knowledge of maintenance and feeding. Characteristics of respondents in terms of age who are still productive with long farming experience. However, marketing is critical because rabbit meat is less popular among the public, so people need to be more familiar with and aware of the processing of rabbit meat.